PENGARUH AUDIT INTERNAL DAN PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PDAM KOTA SURAKARTA - -, SAL Wulandari (Universitas Slamet Riyadi, 2015)
The purpose of this study are: 1) To analyze the direct influence of the internal audit of employee work motivation, 2) analyze the direct influence of the implementation of Good Corporate Governance of employee work motivation. 3) Analyze direct influence on the performance of internal audit staff. 4) Analyze the influence of the direct application of good corporate governance on the performance of employees. 5) Analyze the direct influence of motivation on employee performance. 6) Analyze internal auidt indirect effect on employee performance through motivation as an intervening variable. 7) Analyze the influence of the indirect application of good corporate governance on the performance of employees through motivation as an intervening variable. The population in this study were all employees PDAM Surakarta, amounting to 444 people. The sampling technique used a proportional random sampling. The sample in this study as many as 180 employees. Types of data used quantitative and qualitative data. Data sources using primary data and secondary data. Data collection techniques using questionnaires. Data analysis techniques using test validity, test reliability, test the assumptions of classical and path analysis. Results study showed the value 0,000 p value < 0,05 means that internal audit has a direct influence on employee work motivation. The value 0,002 p value < 0,05 means that GCG has a direct influence on work motivation. The value 0,000 p value < 0,05 means that internal audit has a direct influence on employee performance. The value 0,018 p value < 0,05 means that GCG has a direct influence on employee performance. The value 0,000 p value < 0,05 means that work motivation has a direct impact on employee performance. The direct effect of internal audit variables on performance is (0,330) while the indirect effect on the performance of internal audit through the work motivation is (0,106) so that the internal audit has undirect effect on employee performance through motivation. GCG direct influence on the performance variable is (0,511) while the indirect effect on performance through the implementation of GCG work motivation is (0,164) so the variable GCG has indirect effect on employee performance through motivation to work as intervening variable. Keywords: internal audit, good corporate governance, work motivation, performance